2008
DOI: 10.1291/hypres.31.575
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin Converting Enzyme Inhibitor and Angiotensin II Receptor Antagonist Combination on Nitric Oxide Bioavailability and Atherosclerotic Change in Watanabe Heritable Hyperlipidemic Rabbits

Abstract: We investigated the effects of co-administration of an angiotensin-converting enzyme inhibitor (ACEI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…The present study showed that losartan decreases serum cholesterol, triglyceride, LDL-c and increases HDL-c level, which resembles to the findings of few other studies [23][24] . Hypolipidaemic benefit of losartan in this study might be due to its ability to decrease plasma lipoprotein and fibrinogen level 25 .…”
Section: Discussionsupporting
confidence: 91%
“…The present study showed that losartan decreases serum cholesterol, triglyceride, LDL-c and increases HDL-c level, which resembles to the findings of few other studies [23][24] . Hypolipidaemic benefit of losartan in this study might be due to its ability to decrease plasma lipoprotein and fibrinogen level 25 .…”
Section: Discussionsupporting
confidence: 91%
“…In fact, Yagi et al demonstrated that combined treatment with an ARB, valsartan, and an ACE inhibitor benazepril, had an additive effect on inhibiting neointima formation via improvement of NO production and suppression of oxidative stress in a rat vascular endothelial injury model [82]. We also showed using genetically hyperlipidemic rabbits that chronic administration of either enalapril or losartan increased both ACh-induced and basal plasma NO concentration by using a catheter-type NO sensor [83]. More intriguingly, the combined chronic treatment with enalapril and losartan increased ACh-induced as well as basal plasma NO concentration significantly more than either enalapril or losartan alone [83].…”
Section: Angiotensin-converting Enzyme Inhibitor and Angiotensin Typementioning
confidence: 66%
“…These results suggest that atherosclerosis can be suppressed by normally activated macrophages or normalization of macrophage function. Regarding the anti-atherosclerotic effects of antihypertensive agents on normotensive WHHLMI rabbits, inhibitors of angiotensin converting enzyme 59) and angiotensin-II type I receptor antagonists 60) showed anti-atherosclerotic effects, but not calcium antagonists and beta-blockers. Angiotensin II promotes atherosclerosis through enhancement of cell proliferation, oxidative stress, suppression of arterial endothelial cell function, and inflammation humans.…”
Section: Validation Of the Anti-atherosclerotic Effects Of Various Nomentioning
confidence: 90%